(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article provides basic information about the methods and tools currently used when adding additional floors to existing buildings, assessing the seismic resistance of buildings recommended for reconstruction, and determining the reserves for increasing their seismic resistance. The main part of the article describes in detail the methods for accounting for seismic loads with an increase in the number of storeys of buildings for organizations studying the technical condition of buildings and structures operating on the territory of the Republic of Uzbekistan.